Replacing sulfate with hydroxychloride sources of trace minerals modulated the growth performance and plasma indicators of inflammation and energy metabolism in beef heifers during periods of feed restriction and adaptation to a high-starch diet - Souza, Isabella R. T [UNESP]; Moriel, Philipe; Monar, Gabriel R.R [UNESP]; Lima, Pedro H. L; Carvalho, André A.B.M; Oliva, Guilherme F [UNESP]; Augusto, Karolina V.Z; Porcionato, Marco A.F; Souza, Izadora S; Mackey, Shea J; Cooke, Reinaldo F; Araujo, Davi B; et al. (Oxford University Press (OUP), 2024)
This study evaluated the effects of different sources (sulfate vs. hydroxychloride) of Cu, Mn, and Zn during feed restriction and a high-starch diet on heifer growth performance. On day 0, Nelore heifers (n = 40) were stratified by body weight (BW = 238 ± 38 kg) and age (21 ± 1 mo), and individually allocated into 1 of the 40 drylot pens. The study was divided into periods of pen acclimation (days 0 to 27), nutrient surplus (days 28 to 55), nutrient restriction (days 56 to 83), and step-up adaptation to a high-starch diet (days 84 to 112). Heifers had free choice access to Tifton hay (Cynodon sp.) and salt from days 0 to 27. On day 28, 20 heifers/treatment were randomly assigned to receive free choice access to Tifton hay and protein supplementation at 0.10% of BW (dry matter, DM) added with sulfate (SUL) or hydroxychloride (HYD) sources of Cu, Mn, and Zn from days 28 to 112. From days 56 to 83, heifers were offered 50% of the average hay DM intake obtained from days 50 to 55. From days 84 to 112, each respective protein supplement was mixed with a starch-based total mixed ration and the concentrate DM amount was gradually increased every 7 d (starting with 35% concentrate and 65% hay on day 84 and ending with 80% concentrate and 20% hay from days 106 to 112). Effects of treatment × day and treatment were not detected (P ≥ 0.37) for heifer BW, fecal pH, average daily gain (ADG), and DM intake, except for ADG from days 28 to 56, which was less (P = 0.05) for SUL vs. HYD heifers. Effects of treatment × day were detected (P = 0.02) for plasma concentrations of insulin-like growth factor 1 (IGF-1) and haptoglobin. Plasma concentrations of IGF-1 were greater (P ≤ 0.05) for HYD vs. SUL heifers on days 56, 70, 77, 84, and 91. Plasma concentration of haptoglobin was greater (P = 0.05) for SUL vs. HYD heifers on day 63. Effects of treatment × day of the study and treatment were not detected (P ≥ 0.35) for plasma concentrations of cortisol, ß-hydroxybutyrate (BHBA) and non-esterified fatty acids (NEFA). Thus, Nelore heifers offered hydroxychloride sources of Cu, Mn, and Zn exhibited greater plasma concentrations of IGF-1 and a temporary increase in ADG during nutrient surplus compared to those receiving sulfate sources. While hydroxy¬chloride supplementation reduced the acute phase response early in nutrient restriction, it did not improve growth and plasma concentrations of haptoglobin, cortisol, NEFA, and BHBA during nutrient restriction and adaptation to a high-starch diet.
Keywords: beef heifers; Bos indicus; hydroxychloride; sulfate; trace minerals